Voice matters: Social categorization and stereotyping of speakers based on sexual orientation and nationality categories - Fasoli, F.; Dragojevic, M.; Rakić, T.; Johnson, S. (Language and Communication, 2023)
This research examined how listeners categorize and stereotype speakers belonging to intersecting social categories (nationality; sexual orientation) based on voice alone. In Study 1, British heterosexuals categorized the nationality and sexual orientation of British and Italian speakers who self-identified as gay or heterosexual. Participants correctly categorized British speakers as co-nationals and Italian speakers as foreigners. Categorization accuracy of gay speakers’ sexual orientation was poor. Italian gay speakers were perceived as most likely to be gay and non-native speakers. Study 2 examined stereotyping of speakers who sounded either native or foreign, and sounded either gay or heterosexual. Foreign-accented (vs. native-accented) speakers were rated as less competent, and gay-sounding (vs. heterosexual-sounding) speakers as less gender typical. Foreign-accented gay speakers were perceived as the least competent and gender typical.